2003
DOI: 10.1073/pnas.0531477100
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking natural evolution in vitro : An N -acetylneuraminate lyase mutant with an increased dihydrodipicolinate synthase activity

Abstract: N-acetylneuraminate lyase (NAL) and dihydrodipicolinate synthase (DHDPS) belong to the NAL subfamily of (␤͞␣) 8-barrels. They share a common catalytic step but catalyze reactions in different biological pathways. By rational design, we have introduced various mutations into the NAL scaffold from Escherichia coli to switch the activity toward DHDPS. These mutants were tested with respect to their catalytic properties in vivo and in vitro as well as their stability. One point mutation (L142R) was sufficient to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 38 publications
3
65
0
2
Order By: Relevance
“…The tetramer contains four cysteines, one of which is located on the surface of the tetramer but not fully solvent exposed (21). We observed no chemical protein modification, showing that this compound has low general reactivity and modifies only particularly reactive cysteine residues.…”
Section: Significancementioning
confidence: 67%
See 1 more Smart Citation
“…The tetramer contains four cysteines, one of which is located on the surface of the tetramer but not fully solvent exposed (21). We observed no chemical protein modification, showing that this compound has low general reactivity and modifies only particularly reactive cysteine residues.…”
Section: Significancementioning
confidence: 67%
“…The stabilized DBD of the p53 mutant Y220C (T-p53C-Y220C) and T-p53C cysteine mutants were expressed and purified as described (7). Escherichia coli N-acetylneuraminate lyase was produced as described (21).…”
Section: Methodsmentioning
confidence: 99%
“…7 The fold is very amenable to directed evolution studies as seen in the case of NAL, where DHDPS activity can be gained by a single point mutation (L142R) while NAL activity is retained. 2 Crystal structures of proteins with a DHDPS-like domain have been determined from several organisms. Some of the available PDB models include DHDPS from E. coli 8 (EcDHDPS, PDB: 2ATS), Thermotoga maritima 9 (PDB ID code: 1O5K), Bacillus anthracis 10 (BaDHDPS, PDB ID code: 1XKY), Nicotiana sylvestris 11 (PDB ID code), NAL from E. coli 12 (EcNAL, PDB ID code: 1NAL), Haemophilus influenza 13 (PDB ID code: 1F6K), and KDG aldolase from Sulfolobus solfataricus (SsKDGA, PDB ID code: 1W3I).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the research discipline, some common themes or parameters can be observed in the application of directed evolution. For example, directed evolution increasingly appears to be the tool of choice for studying the evolution of and relationship between protein structure and function (2,114,138,192,226,259) and for interpretation of the evolutionary significance of biomolecular systems (122,323). It is also a popular tool for accelerated adaptation of protein functions (e.g., stability, specificity, or affinity) in extreme conditions such as unusual temperatures and organic solvents (198,204,221,222,(327)(328)(329)(330), as well as for improvement of recombinant protein biosynthesis (152,185).…”
Section: Applications Of Directed Evolutionmentioning
confidence: 99%